CTNI-61. PILOT STUDY OF REPEATED PLANNED GLUCARPIDASE FOLLOWING HIGH DOSE METHOTREXATE (HD-MTX) IN CNS LYMPHOMA (CNSL). (9th November 2020) - Schaff, Lauren; Lobbous, Mina; Sener, Ugur; Gavrilovic, Igor; Miller, Alexandra; Stone, Jacqueline; Piotrowski, Anna; Skakodub, Anna; Madzsar, Juli; Schumpp, Alyssa; Acosta, Edward; Ryan, Kevin; et al.
Abstract: This study explores the repeated use of glucarpidase following HD-MTX in patients with CNSL. HD-MTX requires aggressive hydration and inpatient monitoring to prevent toxicity. Glucarpidase 50 units(u)/kg for delayed MTX clearance results in a reduction of systemic MTX levels without crossing the blood brain barrier. This study explores the use of 1000 or 2000 units of glucarpidase following repeated cycles of MTX 3–8 g/m 2 . Eligible adult patients had isolated CNSL, CrCl ≥ 60 mL/min, and KPS ≥ 50. Rituximab with MTX was administered for eight cycles. Glucarpidase was given 24 hours after each MTX infusion. MTX concentrations were monitored in serum and cerebrospinal fluid (CSF). Twelve patients enrolled to date and data are available for 50 doses of MTX (3 g/m 2 (20), 6 g/m 2 (21), 8 g/m 2 (9)). Glucarpidase 1000u (14) or 2000u (36) resulted in at least a 95% reduction in serum MTX levels within 15 minutes following 49/50 doses. A 93% decrease was seen with the remaining dose. Glucarpidase was not detected in the CSF of 7 patients analyzed. Potentially cytotoxic MTX concentrations (10 –6 M) were observed in CSF 1 hour (7/7) and 6 hours (4/7) after glucarpidase administration. Radiographic responses are evaluable in 9 patients: complete response (5), partial response (2), stable disease (1), and progressive disease (1). No grade 3 events were attributed to glucarpidase; one grade 4 event of anaphylaxis occurred. Anti-glucarpidase antibodies were detected in 2/5 patients analyzed. In summary, administration of low-dose glucarpidase 24 hours after MTX 3–8 g/m 2 results in a reproducible rapid reduction in serum MTX levels in non-renally impaired patients. CSF MTX levels remain therapeutic and clinical response expected from MTX-based therapy does not appear compromised. Anti-glucarpidase antibodies may develop though significance remains unclear. Study is ongoing. Future directions will explore glucarpidase use for reduction of inpatient stay with HD-MTX.